Transport Accessibility of Villages - Ludmila Janosikova; Alexander Kubani (Communications - Scientific letters of the University of Zilina, 2000)
This paper deals with a method for quality analysis of mass transport in a region. Time accessibility of villages was chosen as a quality criterion. The region of Žilina was examined. The combination of bus and train transport was taken into account. Accessibility was examined in dependence on three categories of passengers: irregular passengers, working people and students. The results were analysed using a geographic information system.